The Level of Awareness and Perception of University Students towards Artificial Intelligence in Higher Studies - Dr. Hoori Nadir (International Journal of Indian Psychȯlogy, 2024)
Artificial intelligence stands at the forefront of transformative technology, reshaping educational tools and organizations. In the realm of education, traditionally characterized by the indispensable presence of teachers, the advent of online education and continuous advancements in the Artificial Intelligence (AI) and the machine learning are reshaping the duties of educators. While teachers remain a cornerstone of effective education practices, AI leverages advanced analytics, deep learning, and machine learning to monitor individual progress, differentiating itself from conventional teaching methods. The evolving landscape of AI in education not only facilitates the identification of teaching and learning gaps but also enhances the overall quality of education. As AI solutions progress, they offer a means to identify and address shortcomings in educational delivery, allowing for a more refined and personalized approach to learning. The sublimation of AI into education empowers teachers by developing new time zones adding time and flexibility. This newfound freedom allows educators to rely on developing crucial aspects of understanding and adaptability that require human capabilities, areas where computers may struggle to make an impact. The synergy between AI and human instructors can lead to enhanced efficiency, personalized learning experiences, and streamlined administrative processes. In essence, the convergence of technology and educators holds the potential to extract the best performance from learners. The research article presented here delves into the multifaceted role and impact of AI within the education industry, shedding light on the various modes in which AI can augment educational practices while recognizing the enduring significance of human involvement in the learning process.